Developing climate-smart value chains and landscapes for increased resilient livelihood in West Africa - Project flyer - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This EU-IFAD funded project aims to develop climate-smart value chains and landscapes for increased resilience in Ghana, Mali, Niger and Senegal - Project flyer